Effect of Gamma Radiation on Genetic Diversity Shallots (Allium ascalonicum L.) M4 Bauji Variety For Varieties Improvement - Irfan Satria Anpama; Ida Retno Moeljani; Juli Santoso (Future Science, 2021)
Shallots (Allium ascalonicum L.) is a horticultural commodity that has high economic value in Indonesia. Efforts to increase the productivity and quality of shallots will continue to be carried out through plant breeding programs. One of the efforts is through mutation breeding with the aim of improving the Bauji variety so that it has high yields, good quality and is resistant to major pests and diseases. One of the factors that play a role in increasing shallot production is superior varieties. For the assembly of superior varieties, it is necessary to expand genetic diversity, one of which can be done by radiation mutation. With radiation mutations, new genetic diversity is created so that it provides more opportunities for selection. This research was carried out using the single plant method and using the T-test, with the yield of shallots with radiation doses without radiation doses or 0 Gy, 1 Gy, 2 Gy, 3 Gy, 4 Gy, 5 Gy, 6 Gy. Observation parameters included plant length, number of leaves, number of tillers, tuber diameter, and tuber weight. This study aims to obtain the value of genetic diversity and heritability on the agronomic characters of shallots of bauji variety with 60Co gamma-ray radiation treatment. Gamma-ray irradiation of 60Co affects the growth and yield characteristics of the fourth generation Bauji variety of shallots. Irradiation treatment with a dose of 4 Gy (B4) had better results on the parameters of plant length, number of leaves, tuber diameter, and number of tillers than control plants or without irradiation.